Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I just found this equality on the internet, and I am wondering is there a way to prove it or where I can find the proof ?

$$\displaystyle \frac{ \mathrm d^n}{\mathrm dx^n} {xe^ {rx}} \stackrel{?}{=} ( \frac {n}{r} + x )(r^n)e^{rx}$$

share|improve this question
1  
See section $6$ in this paper for a general technique and examples. –  Mhenni Benghorbal Mar 9 '13 at 16:25
    
By the way, you can try MAPLE to find the nth derivative of some functions with the command diff( f(x), x$n ). –  Mhenni Benghorbal Mar 9 '13 at 16:30
    
Related problem 1, problem 2. –  Mhenni Benghorbal Mar 9 '13 at 16:55
add comment

3 Answers

up vote 1 down vote accepted

You may use Leibniz's rule $$ (fg)^{(n)}=\sum_{k=0}^n {n\choose k} f^{(k)}g^{(n-k)}, $$ where $f^{(k)}$ means the $k$-th derivative of a function $f$ (by convention, $f^{(0)}=f$). Put $f(x)=x$ and $g(x)=e^{rx}$. Then $f^{(k)}(x)=0$ for $k>1$. Hence Leibniz's rule gives $$ (fg)^{(n)}=\sum_{k=0}^{\color{red}1} {n\choose k} f^{(k)}g^{(n-k)} =f(x)g^{(n)}(x)+nf'(x)g^{(n-1)}(x)=xr^ne^{rx}+nr^{n-1}e^{rx}. $$

share|improve this answer
add comment

Suggestion: How about a proof by induction on $n$?

  1. Prove the equality holds for the base case $n = 1$
  2. Assume the equality holds for $n = k, \;\;$ (The Inductive hypothesis)
  3. Show, using the inductive hypothesis, that the equality holds for $n = k+1$. That taking the derivative of the of the the $k^{th}$ derivative gives you the equality of the form needed for $n = k+1$.

Then, once you show you've shown your base case to hold $(1)$, and once you've completed $(3)$, you are justified in concluding that the equation holds for all $n$.

share|improve this answer
    
Let me know if you're familiar with induction proofs. –  amWhy Mar 9 '13 at 4:18
add comment

Lets derive it:

$\displaystyle f(x) = x e^{rx}$

$\displaystyle f'(x) = e^{rx}(rx + 1)$

$\displaystyle f''(x) = r e^{rx}(rx + 2)$

$\displaystyle f'''(x) = r^2e^{rx}(rx + 3)$

$\displaystyle \ldots$

$\displaystyle f^{(n)}(x) = r^{n-1}e^{rx}(rx + n) = \left(\frac{n}{r} + x \right)r^{n}e^{rx}$

share|improve this answer
    
Excellent...show the pattern...generalize! +1 –  amWhy Apr 23 '13 at 0:38
    
@amWhy: While I am at it, I will the same about your answer +1 :-) –  Amzoti Apr 23 '13 at 0:46
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.